Rapid determination of the immobilization conditions for lead and cadmium in soil using 2, 4, 6-trimercaptotriazine, trisodium salt, nonahydrate - Jiang, Ke; Zhou, Kanggen; Zhang, Jiangsheng (Journal of Environmental Engineering and Landscape Management, 2019)
Chemical immobilization is widely used for remediation of heavy metal contaminated soils. The present study proposed a method for the immobilization of lead (Pb) and cadmium (Cd) in soil using 2, 4, 6-trimercaptotriazine, trisodium salt, nonahydrate (TMT). Simulation tests were performed in an aqueous solution to rapidly screen the operational conditions. The effects of TMT dosage, reaction pH, and the coordination ions (Al3+, Fe3+) on immobilization, and the thermodynamics for the TMT-DTPA-Zn-Pb-H2O system, were investigated. The results showed that the immobilization efficiencies of Pb and Cd were removed effectively via the addition of TMT and Fe3+ in the solution containing DTPA. Pb and Cd concentrations decreased from 50 mg/L to <3.9 mg/L and 1.4 mg/L, with a Fe3+/DTPA molar ratio of 0.8 to 2.1, and a TMT dosage of 1.0 mol/mol (Pb and Cd). The screened results in the aqueous solution were used to immobilize Pb and Cd in soil. The extractable concentrations of Pb and Cd in the immobilized soil decreased to 19.6 mg/kg and 1.7 mg/kg, respectively, with a TMT dosage of 2.2 mol/mol (Pb and Cd), and a Fe3+/DTPA molar ratio of 3.6. The bioavailability of Pb and Cd met the environmental quality standard for drylands in China (GB 15618-1995). The results demonstrated that remediation conditions could be rapidly screened in an aqueous solution rather than soil. The method using TMT and ferric sulfate was potentially effective in immobilizing Pb and Cd.